Peran Probiotik dalam Regulasi Kolagen dan Melanin: Systematic Review - Badri, Amelia A.; Dewi, Ni Nyoman Ayu; Wahyuniari, Ida Ayu Ika (Jurnal Kesehatan Andalas, 2024)
Collagen and melanin production are two biological processes that are significant in determining the health and appearance of the skin. Collagen affects the elasticity, hydration, and overall appearance of the skin. Melanin protects the skin from damage caused by ultraviolet rays, but excessive production can lead to hyperpigmentation. Hyperpigmentation, dry skin, and wrinkles are signs of premature aging and can be caused by oxidative stress due to exposure to UV rays (photoaging). Probiotics are living microorganisms that provide health benefits when consumed in sufficient amounts and are currently gaining more and more attention as potential agents for skin health. This article reviews the role of probiotics in inhibiting melanogenesis through inhibition of tyrosinase cell activity and microphthalmia-associated transcription factor (MITF) expression. Probiotics can slow down collagen degradation due to sunlight by inhibiting the Metalloproteinase Matrix (MMP) activity and improve the skin's barrier function, reduce inflammation, and support a healthy skin microbiota. Recent studies show that the use of probiotics, both oral and topical, offers a natural and multifunctional approach to skin care. In conclusion, probiotics have promising potential as an ingredient for skincare, but more research is needed to understand the underlying mechanisms and ensure their safety and effectiveness in clinical applications. Keywords: hyperpigmentation, melanogenesis, photoaging, probiotics